Both open and endoscopic gluteal tendon repairs lead to functional improvement with similar failure rates: a systematic review. Issue 1 (24th September 2020) - Longstaffe, Robert; Dickerson, Patrick; Thigpen, Charles A; Shanley, Ellen; Kissenberth, Michael J; Folk, Jason; Pill, Stephan G
Abstract : Importance: Operative treatment of gluteal tendon tears is becomingly increasingly more common with varying surgical techniques and rehabilitation protocols. Objective: To perform a systematic review of gluteal tendon repair as it relates to tear characteristics, rehabilitation protocols, patient-reported outcomes, satisfaction, resolution of gait deviation and complication rates. Evidence review: A comprehensive literature search of PubMed and Embase/MEDLINE was used to identify all literature pertaining to gluteal tendon repair. A total of 389 articles were identified. Findings: A total of 22 studies (611 hips) were included in this review. The majority of tears were noted to be partial thickness (77.9% vs 22.1%). Both arthroscopic and open repair demonstrated improvements in functional outcomes. Within studies documenting gait deviation, 54% were noted to have gait deviation preoperatively, of which approximately 70% had resolution following repair. On average, abduction strength increased almost one whole grade (0.84) following repair. Overall complication rate was found to be 5.2% (20 of 388 hips). Endoscopic repair demonstrated a decreased complication rate compared with open (0.7% vs 7.8%). Retear rate was found to be 3.8%, with open repair having a slightly increased rate compared with endoscopic repair (3.4% vs 4.1%). Conclusions and relevance: The majority of tears tend to be partial thickness with involvement of gluteus medius in almost all cases and concomitant involvement of gluteus minimus in close to half of cases. Both endoscopic and open gluteal tendon repairs resulted in improvements in outcomes and functional improvement. Retear rates were similar between the two repair techniques, while endoscopic repair demonstrated a lower complication rate. Level of evidence: Level IV, systematic review.